2006
DOI: 10.1097/01.ta.0000202714.31780.5f
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Biking Injuries Requiring Trauma Center Admission: A 10-year Regional Trauma System Experience

Abstract: Mountain biking is a growing cause of serious injuries. Young males are principally at risk and serious injuries result from intended activity and despite protective equipment. Injury prevention programs were developed to address these concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 13 publications
4
91
4
2
Order By: Relevance
“…Although the orthopedic injury rate approximated those observed in previous investigations, [4][5][6]22,23 the frequency of thoracic injuries was significantly higher. This most commonly comprised rib fractures, pulmonary contusions and hemopneumothoraces.…”
Section: E35mentioning
confidence: 38%
See 3 more Smart Citations
“…Although the orthopedic injury rate approximated those observed in previous investigations, [4][5][6]22,23 the frequency of thoracic injuries was significantly higher. This most commonly comprised rib fractures, pulmonary contusions and hemopneumothoraces.…”
Section: E35mentioning
confidence: 38%
“…The rate of spinal trauma was significantly higher among mountain than street cyclists (65.3% v. 41.1%, p = 0.003), with fractures to the cervical and thoracolumbar spine being equally frequent. 5 A potential mechanism for concomitant head and cervical spine injury in mountain bikers has previously been postulated to involve a fall over the handlebars, resulting in a blow to the top of the head and cervical flexion or hyperextension. 5,21 This mechanism may easily have occurred in this study, given that so many mountain bikers were observed to fall off cliffs, roadsides and embankments.…”
Section: E35mentioning
confidence: 99%
See 2 more Smart Citations
“…Although no studies published till date have been specifically performed in climbers, there is some evidence that males may be at greater risk for acute injuries in mountain biking [8]. Also, males are inclined to take greater risks in rock climbing [9] which may be explained by their mean risk perception being generally lower than that of women in outdoor-adventure sports [10,11].…”
Section: Introductionmentioning
confidence: 97%